2019
DOI: 10.3389/fped.2019.00101
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Surgical Site Infection in Neonates: A Systematic Review of the Literature and Meta-Analysis

Abstract: Purpose: Surgical site infections (SSI) contribute to postoperative morbidity and mortality in children. Our aim was to evaluate the prevalence and identify risk factors for SSI in neonates. Methods: Using a defined strategy, three investigators searched articles on neonatal SSI published since 2000. Studies on neonates and/or patients admitted to neonatal intensive care unit following cervical/thoracic/abdominal surgery were included. Risk factors were identified from compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 70 publications
(63 reference statements)
1
16
0
12
Order By: Relevance
“…However, recent studies show that prolonged antibiotic exposure in infants could result in serious side effects: antibiotics alter gut microbiota, increase risk of necrotizing enterocolitis, late onset sepsis and even death [173 , 174] . Additionally a recent systematic review showed that pre-operative antibiotic treatment did not influence the occurrence of surgical site infections in neonates [175] . Yet, this lack of effectiveness in neonates could be explained by a lack of appropriate timing of administration, which could be improved by correct protocol adherence [177] .…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies show that prolonged antibiotic exposure in infants could result in serious side effects: antibiotics alter gut microbiota, increase risk of necrotizing enterocolitis, late onset sepsis and even death [173 , 174] . Additionally a recent systematic review showed that pre-operative antibiotic treatment did not influence the occurrence of surgical site infections in neonates [175] . Yet, this lack of effectiveness in neonates could be explained by a lack of appropriate timing of administration, which could be improved by correct protocol adherence [177] .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the national pooled prevalence of SSI was 11.58 (95% CI 9.78, 13.38). This result was relatively higher than annual epidemiological report for 2016 of SSI by European Centre for Disease Prevention and Control (ECDC) ranged between 0.5% to 9.0%, depending on the type of surgical procedure [43]; and from meta analysis result of SSI among neonates (5.6%) [44] and in China (4.5%) [45]. The lower prevalence of SSI in developed counties may be due to strong economies, having a high set up hospitals, their degree of adherence to aseptic techniques and surgical procedure may be done by well experienced surgeons.…”
Section: Discussionmentioning
confidence: 70%
“…In paediatric patients, proper administration of preoperative antibiotics is also widely accepted as one of the few risk factors which can be influenced [17] . However, ambiguity on this effect exists in neonates [18] . This is possibly explained by a lack of appropriate timing of perioperative antibiotic administration, as a result of improper protocol adherence or even the absence of protocols [19] .…”
Section: Discussionmentioning
confidence: 99%